Efficacy of Mindfulness-Based Stress Reduction on Reducing Somatization and Attachment Anxiety: A Randomized Controlled Trial - Li, Jinghua; Zhou, LuXin (Journal of Personality and Psychosomatic Research (JPPR), 2024)
The objective of this study was to evaluate the effectiveness of Mindfulness-Based Stress Reduction (MBSR) in reducing symptoms of somatization and attachment anxiety in adults. This randomized controlled trial involved 30 participants, divided equally into an MBSR intervention group and a control group. Participants were assessed at baseline, post-intervention (12 weeks), and at a two-month follow-up using the Patient Health Questionnaire-15 (PHQ-15) and the Experiences in Close Relationships-Revised (ECR-R) questionnaire. Data were analyzed using Analysis of Variance (ANOVA) with repeated measures and Bonferroni post-hoc tests, employing SPSS version 27. The MBSR intervention group showed a significant reduction in somatization from a baseline mean of 15.40 (SD = 2.58) to 8.25 (SD = 1.93) post-intervention and 9.10 (SD = 2.05) at follow-up (p < .001). The control group showed no significant changes. Similarly, attachment anxiety in the intervention group decreased from a baseline mean of 18.60 (SD = 2.73) to 12.70 (SD = 2.35) post-intervention and 13.40 (SD = 2.48) at follow-up (p < .001), while the control group remained stable. The results demonstrate that MBSR is an effective intervention for reducing somatization and attachment anxiety. These findings support the integration of MBSR into therapeutic practices for individuals experiencing these conditions.